Nutritional Status and Blood Biochemical Parameters in Anoestrus Crossbred Cattle in Malwa Region of Madhya Pradesh - Tewari, Dharmesh; Jain, R.K.; Dhakad, R.K. (Indian Journal of Animal Nutrition, 2018)
Reproductive failure is a major problem in crossbred cattle in Malwa region of Madhya Pradesh. To find out the nutritional causes behind anoestrus, thirty anoestrus crossbred cattle including 20 heifers (BW224.75±7.41 kg) and 10 cows (BW 316.50±15.48 kg; milk yield 4.9±1.25 L/h/d) were randomly selected from ten villages of Indore district. The average daily feed intake of each animal was recorded and proximate principles, major elements (Ca and P) and trace elements (Fe, Zn, Mn, Cu and Co) in the available feedstuffs were determined to find out nutrient availability. Deficiency of various nutrients was calculated by comparing availability with standard requirements of the animals. Blood samples were also collected and analyzed for different haemato-biochemical constituents. The average values for Hb 9.19±0.20 and 10.34±0.28 g/dL; blood glucose, 49.29±0.91 and 55.73±1.42 mg/dL; plasma protein 5.05±0.09 and 6.80±0.26 g/dL were found in heifersand cows, respectively. Major mineral profile in heifers and cows were Ca, 9.65±0.17 and 8.81±0.29 mg/dL; P 5.12±0.14 and 5.12±0.34 mg/dL; Total P 15.50±1.14 and 24.00±2.21 mg/dL, respectively. Trace mineral levels in heifers and cows were Fe 24.35±2.12 and 18.96±1.43 ppm; Zn 1.45±0.07 and 1.62±0.09 ppm; Cu 0.65±0.06 and0.91±0.12 ppm; Mn 0.74±0.10 and 0.86±0.07 ppm; Co 1.82±0.30 and 2.54±0.44 ppm, respectively. Results indicated that values of Hb, blood glucose, total protein, Ca, P, Zn were marginally lower but Cu was deficient in heifers while in cows the levels of Ca, P and Zn were marginally lower. Fe levels were found to be high in both heifers and cows. It may be concluded that dietary deficiency reflected the hemato-biochemical profile of anoestrus animals and a nutrient mixture has been prepared for minimization of anoestrus in crossbred cattle.